Desigualdade socioambiental no espaço urbano de guarapuava - De Freitas Vilas Boas Gomes, Marquiana [UNESP] (My University, 2010)
This article aims at discussing urban environmental quality. This includes making the result of mapping the city's environmental quality of Guarapuava - PR. In making the statement were considered census data from IBGE (2000), concerning the distribution of water, sanitary sewer services, garbage collection, improvised dwellings, and also the mapping of urban green areas. From the collected data indices of environmental quality were generated. The data indicated that there is an uneven socio-spatial materialized within the city of Guarapuava. Considering also the distribution of income, the analysis revealed a close relationship between social inequality and environmental injustice.
Environmental inequality in the urban space of guarapuava
Keywords: Environmental injustice; Environmental quality; Guarapuava; Urban space